A rare case of a primary hepatic neuroendocrine tumor - Sethi, Sajiv (Transl Gastroenterol Hepatol, 2016)
Neuroendocrine tumors are well-differentiated low grade malignant neoplasms. Their pathogenesis is thought to be secondary to the unrestricted proliferation of neuroendocrine cells. They most commonly arise in the bronchopulmonary or gastrointestinal tract but can originate from almost any organ. While the liver is a common site of metastases, primary hepatic neuroendocrine tumors are an exceedingly rare pathology, of which fewer than 100 cases have been described in world literature. Thus, there exists a paucity of data regarding the clinical presentation, diagnosis and management of this disease. We present a case of a 35-year-old patient who presented to our facility for evaluation of a cough and cervical lymphadenopathy. Two biopsies of the lymph nodes were negative, however on workup for an occult malignancy a hypodense heterogeneous hypervascular lesion measuring 3.7 cm × 2.7 cm in segment IVb of the liver was noted on computer tomography (CT) scan. The levels of laboratory studies such as liver enzymes, alkaline phospatase, chromogranin A, 24-hour 5 hydroxyindoleacetic acid (5-HIAA) and tumor markers including alpha fetoprotein were not elevated. An MRI confirmed the mass, and the patient underwent CT guided biopsy of the hepatic lesion. Staining from the biopsy resulted in cells reactive for synaptophysin, chromogranin, anti-Cytokeratin (CAM 5.2), MOC31, CD 56 and mucin glycoprotein (MUC) confirming a nonsecretory neuroendocrine tumor. Patient underwent octreotide scan, PET scan, CT chest, MRI head along with EUS, EGD and colonoscopy to evaluate for a primary source, however, none was found. The well localized presentation without extensive hepatic invasion made the patient a candidate for surgical resection which was successfully performed. The patient remains disease free over 36 months after initial presentation. Primary hepatic neuroendocrine tumors are an exceedingly rare entity whose variable presentation necessitates provider familiarity with this condition. Once identified, excluding other primary locations with thorough investigation and treatment with surgical resection has been shown to provide the most patient benefit.